(untitled) (Academia Science Repository, 2023)
Currently, it is very important to provide high-quality environmental education to children. This is because the ecological situation on our planet and in our country leaves much to be desired. Many environmental problems: depletion of the ozone layer, climate change, erosion of the natural soil layer, depletion of drinking water and natural resources, high concentrations of pollutants in the air - this is mainly the result of the lack of proper. the interaction of man and nature. Also, these problems are related to the process of educating the population - its inadequacy and complete absence caused the consumer’s attitude to nature. The only way out of this situation is to acquire ecological culture. And it is necessary to start instilling this culture in school children. This is of great social importance to the whole society! In addition, a significant part of the adult population - pedagogues, parents, teachers - is included in this process, which is important for the general ecologicalization of consciousness and thinking.